Presentism remains - Tallant, Jonathan (Springer, 2017)
Here I examine some recent attempts to provide a new way of thinking about the philosophy of time that question the central role of ‘presentness’ within the definition of presentism. The central concern raised by these critics turns on the intelligibility and theoretical usefulness of the term ‘is present’ (cf. Correia and Rosenkrantz in Thought 4:19–27, 2015; Deasy in Nous, 2017. https://doi.org/10.1111/nous.12109; Williamson in Modal logic as metaphysics, OUP, Oxford, 2013). My overarching aim is to at least challenge such concerns. I begin with arguments due to Deasy (Nous, 2017. https://doi.org/10.1111/nous.12109). Deasy develops a view that he calls ‘transientism’ and that he takes to be a well-motivated version of presentism. I show that both this way of thinking about presentism and the argument supposedly motivating it all fail. I then move to an argument due to Correia and Rosenkrantz (Thought 4:19–27, 2015). Correia and Rosenkrantz purport to show that presentism can be salvaged without making recourse to the term ‘is present’. I demonstrate that their arguments fail. I then move on to a view, proposed and defended by Merricks (Truth and ontology, OUP, Oxford, 2007), Tallant (Erkenntnis 79:479–501, 2014), and Zimmerman (Philos Pap 25:115–126, 1996), and show that it has the wherewithal to meet the challenges raised by Williamson (Modal logic as metaphysics, OUP, Oxford, 2013) who, as noted above, raises genuine concerns about our capacity to define presentism.